Reproductive Technologies and Epigenetics: their Implications for Genomic Selection in Cattle - Patrice Humblot (Acta Scientiae Veterinariae, 2011)
Background: The development of genomic selection allowing a better selection for multiple traits (both for production and functional traits) induces dramatic changes in the way selection schemes are to be conducted. The associated needs for genomic selection which is to produce a large number of genotyped candidates as quick as possible may/will influence the way reproductive techniques are used to produce them. As the effect of the environment is no more integrated in the evaluation of performances based on genotype, there is also a need to better understand epigenetic effects and their possible implications while implementing genomic selection. Review: Information brought by reproductive physiology through access to powerful research tools in the fields of genomics, transcriptomics, proteomics and metabolomics will provide new genetic markers and will contribute to improve the precision of phenotypes. The combination of the two types of information is susceptible to increase considerably the efficiency of selection for reproductive traits. As better reproduction may facilitate the way to run selection schemes (more choice among candidates and production of those candidates at a young age), this knowledge can be profitable also to increase the efficiency of multiple trait selection. In this context, and depending on population characteristics, the interest of the reproductive techniques including assisted embryo based reproductive technologies (Multiple Ovulation Embryo Transfer (MOET) and Ovum pick up associated to in vitro Fertilization (OPU-IVF)) should be also revisited. The efficiency of systems based on scenarios involving several reproductive techniques taken in combination should be tested. The recent results obtained with embryo typing, which are compatible with the use of the last generation of chips for genotype analysis may lead to very promising applications for the breeding industry. The combined use of several embryo based reproductive technologies will probably be more important in the near future for selection purposes to satisfy the needs of genomic selection by increasing the number of candidates and to preserve at the same time genetic variability. Since several years, genotyping has been used more or less intensively by breeding companies to genotype males and females within nucleus herds As any farmer will get access to the genotype of the females present in their herd, an increased use of embryo based reproductive technologies may result also from the demand of individual farmers who may wish to valorize as well and as quick as possible the genetic potential of their best heifers following genotyping. In the near future, a better knowledge on epigenetics will allow to estimate the interactions between genotype and environment and their impact on performances of present or future generations. This represents a critical information when evaluating performances and when selecting future sires on genomic based information espe